2013
DOI: 10.1002/hed.23510
|View full text |Cite
|
Sign up to set email alerts
|

Bone impacted fibular free flap: A novel technique to increase bone density for dental implantation in osseous reconstruction

Abstract: BIFFF increases reconstructed bone density, initial dental implant stability, and 1-year implant success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…3,5 The bone stock can be further augmented for implantation by impacting the marrow of the donor fibula with demineralized bone or morselized fibular bone, resulting in improved osseointegrated implant longevity. 46,47 The present study has certain limitations. The prospective cohort case-matched design confers level 2-3 evidence and is the best design possible with our longitudinal data.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…3,5 The bone stock can be further augmented for implantation by impacting the marrow of the donor fibula with demineralized bone or morselized fibular bone, resulting in improved osseointegrated implant longevity. 46,47 The present study has certain limitations. The prospective cohort case-matched design confers level 2-3 evidence and is the best design possible with our longitudinal data.…”
Section: Discussionmentioning
confidence: 83%
“…The fibula is the most commonly used flap in the bone framework reconstruction of the head and neck, as it provides excellent bone stock, good soft tissue component, and has a long, robust pedicle . The bone stock can be further augmented for implantation by impacting the marrow of the donor fibula with demineralized bone or morselized fibular bone, resulting in improved osseointegrated implant longevity …”
Section: Discussionmentioning
confidence: 99%
“…This technique involves morselization of the remaining fibula and impaction of the pieces into the hollow marrow of the fibula bone before insetting. A previous study describing the technique demonstrated increased bone density at 6 and 12 months after BIFFF reconstruction, as assessed on CT imaging. The justification for this procedure is the desire for increased bone stock provided by the impaction that may contribute to more successful osseointegration of the surface area of the implant compared to the traditional fibular free flap, which relies on only the fibular cortical plates for osseointegration.…”
Section: Introductionmentioning
confidence: 83%
“…The BIFFF is harvested, as previously described by Dziegielewski et al The fibula bone is cut to the appropriate length necessary to reconcile the defect and hollowed, after which the remaining bone is cut into smaller pieces and morselized. The morselized bone is then rinsed with 20 cc of sterile 0.9% isotonic saline.…”
Section: Methodsmentioning
confidence: 99%
“…With an osseous component, osseointegrated implants for future dental rehabilitation can be pursued. 13 Several different osseous flaps have been used and include the fibular osteocutaneous flap, [13][14][15][16][17][18][19] iliac crest flaps, 20 and scapular flaps. [21][22][23] Studies on speech outcomes have shown that maxillary reconstruction results in satisfactory speech 22,24,25 and normal intelligibility.…”
Section: Introductionmentioning
confidence: 99%